2021
DOI: 10.3389/fpsyg.2021.680882
|View full text |Cite
|
Sign up to set email alerts
|

Infants’ Implicit Rhyme Perception in Child Songs and Its Relationship With Vocabulary

Abstract: Rhyme perception is an important predictor for future literacy. Assessing rhyme abilities, however, commonly requires children to make explicit rhyme judgements on single words. Here we explored whether infants already implicitly process rhymes in natural rhyming contexts (child songs) and whether this response correlates with later vocabulary size. In a passive listening ERP study, 10.5 month-old Dutch infants were exposed to rhyming and non-rhyming child songs. Two types of rhyme effects were analysed: (1) E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
(113 reference statements)
0
1
0
Order By: Relevance
“…One possible reason for such time-wise imbalanced selectivity was that the rhythmic features in SP speech could be integrated in a short time and facilitate semantic retrieval. In EEG studies that had a high temporal resolution, prosodic information, such as rhyme congruity ( Chen et al, 2016 ; Hahn et al, 2021 ) was shown to be processed as early as 200 ms after stimuli onset. Its temporal priority in the auditory speech processing was much higher than that of syntactic and semantic information which have been claimed to be processed in the late time window of 400–1,000 ms, i.e., widely recognized ERP components of N400 and P600 ( Zhang et al, 2013 ; Delogu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…One possible reason for such time-wise imbalanced selectivity was that the rhythmic features in SP speech could be integrated in a short time and facilitate semantic retrieval. In EEG studies that had a high temporal resolution, prosodic information, such as rhyme congruity ( Chen et al, 2016 ; Hahn et al, 2021 ) was shown to be processed as early as 200 ms after stimuli onset. Its temporal priority in the auditory speech processing was much higher than that of syntactic and semantic information which have been claimed to be processed in the late time window of 400–1,000 ms, i.e., widely recognized ERP components of N400 and P600 ( Zhang et al, 2013 ; Delogu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%